Assessing the potential of wild foods to reduce the cost of a nutritionally adequate diet: an example from eastern Baringo District, Kenya - Termote, Céline; Raneri, Jessica Evelyn; Deptford, A.; Cogill, Bruce (Nevin Scrimshaw International Nutrition Foundation, 2014)
A study of the role of wild food biodiversity in achieving a cost reduction of a nutritionally adequate diet for women and young children in Kenya using linear programming.An ethnobiological inventory of available food biodiversity was carried out by means of focus group discussions, and five wild foods selected for further modeling. A market survey assessed available food prices by season. Diets were modeled to minimize cost and maximize nutrient adequacy using the Cost of Diet linear programming tool. Modeling was done without and with wild foods.The modeled diets without wild species were deficient in iron for all age groups during the dry season, deficient in vitamin B6 and calcium for infants aged 6 to 8 months during the dry season, and deficient in iron and zinc for infants aged 6 to 8 months over the whole year. Adding wild foods to the modeled diets resulted in a lower-cost diet, while meeting recommended iron intakes for women and children between 12 and 23 months of age.